Gender and diversity in assessing sustainable forest management and human well-being: reflections on assessment methods tests conducted in Bulungan, East Kalimantan, Indonesia - McDougall, C. (Resources for the Future and Center for International Forestry Research, 2001)
Gender and human diversity are critical aspects of sustainable forest management and human well-being. This chapter draws on experiences of a criteria and indicators (human well-being assessment) methods test in Kalimantan, Indonesia, to explore these concepts, and gender and diversity analysis in relation to sustainability in forestry, specifically in terms of the role of such analysis in human well-being assessments for research and management. Some of the key theoretical underpinnings of gender and diversity analysis are highlighted, including the potential tensions between the two elements. These tensions, however, are resolvable if gender is approached conceptually as existing at both the macro and micro levels; in the former creating “space” for diversity and in the latter as one of many forms of diversity. The need to emphasise relations in gender and diversity analysis, instead of just roles, is also critical. Taking a gender and diversity approach in the assessment of human well-being in Kalimantan required creativity and flexibility in design and implementation. The chapter addresses these through three lenses: “assessor” awareness, or “grounding oneself”; the assessment tool (in this case the CIFOR C&I Generic Template); and challenges and strategies for accessing local people’s participation. The human well-being assessment test experience in Kalimantan, and other experiences in forestry and natural resource management, indicate that gender and diversity approaches increase the accuracy of assessments, and thus the ultimate effectiveness of research and forestry initiatives. The fundamental connection of gender and diversity analysis to issues of equity, and the links to participation and empowerment also reveal the potential potency of such analysis in promoting social change.